1987
DOI: 10.1002/chin.198719208
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Novel System: 2H‐Pyrido(3,2‐e)‐1,2‐thiazine‐1,1‐dioxide. Synthesis and Properties of Some Derivatives.

Abstract: The pyridoisothiazoline (Ia) reacts with sodium ethoxide to give the nicotinic acid (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The new derivatives were obtained as a result of multistage synthesis, as shown in Figure 2. The key intermediate ethyl ester of 3-benzoyl-4-hydroxy-5,7-dimethyl-2H-pyrido[3,2-e]-1,2-thiazine-1,1-dioxide-2-acetic acid (1) was obtained by a few reactions, which have been described in the literature [50,51]. Ester (1) was easily converted into pyridothiazine-1,1-dioxide-2-acetic acid hydrazide (2) in a reaction with hydrazine hydrate.…”
Section: Synthesis Of New 134-oxadiazole Derivatives Of Pyridothiazmentioning
confidence: 99%
“…The new derivatives were obtained as a result of multistage synthesis, as shown in Figure 2. The key intermediate ethyl ester of 3-benzoyl-4-hydroxy-5,7-dimethyl-2H-pyrido[3,2-e]-1,2-thiazine-1,1-dioxide-2-acetic acid (1) was obtained by a few reactions, which have been described in the literature [50,51]. Ester (1) was easily converted into pyridothiazine-1,1-dioxide-2-acetic acid hydrazide (2) in a reaction with hydrazine hydrate.…”
Section: Synthesis Of New 134-oxadiazole Derivatives Of Pyridothiazmentioning
confidence: 99%
“…In continuation of our research groups’ work in the field of synthetic organic chemistry [ 1 , 2 , 3 , 4 , 5 ]; we would like to report here on the annulation of isothiazole, 1,3-thiazine and 1,4-thiazepine ring systems to pyridine. Promising biological activities are reported in the literature concerning the targeted ring systems: Isothiazolo[5,4-b]pyridines could be used as analgesics [ 6 , 7 ] and as CNS and antimicrobial agents [ 8 ], pyrido[3,2-e][1,3]thiazines could be used as CNS and antioxidant agents [ 9 ] and as analgesic agents [ 10 ] and pyrido[3,2-f]-[1,4]-thiazepines were used as calcium antagonists in both cardiac and smooth muscles [ 11 ] and as channel blockers for treatment of cardiovascular diseases [ 12 ]. Microwave-assisted technique offer several advantages over conventional methods of synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the transformation of the nitrile group as a substituent in the pyridine ring into an amide [4], ester [5], or acid group [6] requires relatively rigorous conditions, similar to most reactions of nitriles [7].…”
mentioning
confidence: 99%
“…On the other hand, the transformation of the nitrile group as a substituent in the pyridine ring into an amide [4], ester [5], or acid group [6] requires relatively rigorous conditions, similar to most reactions of nitriles [7].We have found that cyclopentylidenecyanoacetamide 1a and cyclohexylidenecyanoacetamide 1b react under conditions of the Michael reaction with acetoacetanilide 2a or ethyl acetoacetate 2b to give functionalized spiro-substituted 1,2,3,4-tetrahydronicotinamides 3a,b in good yields.The mechanism for the transformation of the nitrile group into an amide group, the scope of this reaction, and the chemical and biological properties of products 3a,b are under investigation. O NH 2 NC O R O Me NH O NH 2 N H Me O O R ( ) n + ( ) n 1a,b 2a,b 3a,b EtOH, 20 o C 1, 3 а n = 1, b n = 2; 2, 3 a R = PhNH, b R = EtO…”
mentioning
confidence: 99%